Coping strategies of rubber farmers in Bueng Kan, Thailand during a period of price fluctuations - Neadkhun, Piyanead; Borisutdhi, Yos; Simarak, Suchint; Panpakdee, Chaiteera (Humanities, Arts and Social Sciences Studies, 2023)
The purpose of this study was to analyze the coping strategies applied to mitigate the impact of rubber price fluctuations. To achieve this, 98 rubber farmers in Nonsa village located in the province of Bueng Kan were selected to determine their coping strategies and to identify the determinants influencing their decisions. The study reveals the existence of six coping strategies, all of which were aimed at strengthening their self-dependence in various forms. They minimize fertilizer costs by reducing the number of times they would apply it. The available household labor is engaged, while the costs to hire other labor to sufficiently handle production are lowered because some of the tasks, such as tapping, is amended from the traditional system of 2d/3 to the half-spiral (S/2). In addition, short cycle home-grown crops and livestock are introduced on unused lands to generate both a valuable food supply and manure. In brief, these coping strategies were developed to create an equilibrium between their household expenditures and the agricultural revenues to nurture the farmers’ well-being when experiencing a state of economic hardship. However, to maintain these coping strategies against unexpected uncertainty, specific knowledge about how to build resilience should be creatively facilitated. Resilient rubber farmers are required to cope with all kinds of change to sustain their farms’ functions, structures, and operations in the same domain.